Association between the 21-gene recurrence score and isolated locoregional recurrence in stage I-II, hormone receptor-positive breast cancer - Yang, David D. (Radiat Oncol, 2020)
BACKGROUND: Although the 21-gene recurrence score (RS) assay is widely used to predict distant recurrence risk and benefit from adjuvant chemotherapy among women with hormone receptor-positive (HR+) breast cancer, the relationship between the RS and isolated locoregional recurrence (iLRR) remains poorly understood. Therefore, we examined the association between the RS and risk of iLRR for women with stage I-II, HR+ breast cancer. METHODS: We identified 1758 women captured in the national prospective Breast Cancer-Collaborative Outcomes Research Database who were diagnosed with stage I-II, HR+ breast cancer from 2006 to 2012, treated with mastectomy or breast-conserving surgery, and received RS testing. Women who received neoadjuvant therapy were excluded. The association between the RS and risk of iLRR was examined using competing risks regression. RESULTS: Overall, 19% of the cohort (n = 329) had a RS ≥25. At median follow-up of 29 months, only 22 iLRR events were observed. Having a RS ≥25 was not associated with a significantly higher risk of iLRR compared to a RS < 25 (hazard ratio 1.14, 95% confidence interval 0.39–3.36, P = 0.81). When limited to women who received adjuvant endocrine therapy without chemotherapy (n = 1199; 68% of the cohort), having a RS ≥25 (n = 74) was significantly associated with a higher risk of iLRR compared to a RS < 25 (hazard ratio 3.66, 95% confidence interval 1.07–12.5, P = 0.04). In this group, increasing RS was associated with greater risk of iLRR (compared to RS < 18, hazard ratio of 1.66, 3.59, and 7.06, respectively, for RS 18–24, 25–30, and ≥ 31; P(trend) = 0.02). CONCLUSIONS: The RS was significantly associated with risk of iLRR in patients who did not receive adjuvant chemotherapy. The utility of the RS in identifying patients who have a low risk of iLRR should be further studied.